Resources and Risks of Moderation as an Interactive Method of Furthering Teamwork Skills among Students of Higher Education Institutions - Tatyana T. Sidelnikova (National Research Mordova State University, 2018)
Introduction. The article presents moderation in the organisation of the educational process. Moderation contributes to the development of communicative competencies in students. Graduates with developed communicative skills are in demand by the labor market and are attractive to employers. The purpose of the article is to investigate the development of team skills, the advantages of moderation, its risks and ways to overcome them, to discover the dynamics of students' attitudes toward group forms of organisation of training before and after their use. Materials and Methods. Systemic and structural-functional approaches, sociological, logical and comparative methods were used as methodological grounds of the study. The empirical methods included observation, questioning, testing, analysis, study, and generalisation of the results. Results. The relevance of moderation in teaching learning process has been substantiated. This method promotes the development of teamwork skills among students. At the same time, several risks were diagnosed. The different value attitude of students towards joint activity and personal contribution to the overall result, absolutisation of comfortable relations in the team, and the incompetent formation of teams are the main risks. Competent application of moderation creates a positive dynamics of growth of interest and readiness of students to collective methods of teaching. Awareness of the importance of teamwork leads to greater effectiveness in the activity. The revealed positive dynamics of students' attitude to group methods in teaching learning process testifies to the relevance of the application of new methods. Discussion and Conclusions. The results of the study can be used by lectures interested in modern teaching technologies. In addition, employees of university departments involved in the implementation of innovations in the teaching learning process will find much important and u seful information in this article.